Movement of Chronic Wasting Disease Prions in Prairie, Boreal and Alpine Soils - Alsu Kuznetsova; Debbie McKenzie; Bjørnar Ytrehus; Kjersti Selstad Utaaker; Judd M. Aiken (Pathogens, 2023)
Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy negatively impacting cervids on three continents. Soil can serve as a reservoir for horizontal transmission of CWD by interaction with the infectious prion protein (PrPCWD) shed by diseased individuals and from infected carcasses. We investigated the pathways for PrPCWD migration in soil profiles using lab-scale soil columns, comparing PrPCWD migration through pure soil minerals (quartz, illite and montmorillonite), and diverse soils from boreal (Luvisol, Brunisol) and prairie (Chernozem) regions. We analyzed the leachate of the soil columns by immunoblot and protein misfolding cyclic amplification (PMCA) and detected PrP in the leachates of columns composed of quartz, illite, Luvisol and Brunisol. Animal bioassay confirmed the presence of CWD infectivity in the leachates from quartz, illite and Luvisol columns. Leachates from columns with montmorillonite and prairie Chernozems did not contain PrP detectable by immunoblotting or PMCA; bioassay confirmed that the Chernozemic leachate was not infectious. Analysis of the solid phase of the columns confirmed the migration of PrP to lower layers in the illite column, while the strongest signal in the montmorillonite column remained close to the surface. Montmorillonite, the prevalent clay mineral in prairie soils, has the strongest prion binding ability; by contrast, illite, the main clay mineral in northern boreal and tundra soils, does not bind prions significantly. This suggests that in soils of North American CWD-endemic regions (Chernozems), PrPCWD would remain on the soil surface due to avid binding to montmorillonite. In boreal Luvisols and mountain Brunisols, prions that pass through the leaf litter will continue to move through the soil mineral horizon, becoming less bioavailable. In light-textured soils where quartz is a dominant mineral, the majority of the infectious prions will move through the soil profile. Local soil properties may consequently determine the efficiency of ...